(untitled) (Applied Biological Research, 2024)
The bioactivity of broccoli microgreens might be valuable for understanding the association between diet and cancer along with searching for healthy and functional food options. The present study was centred on broccoli microgreens as a functional food. The anticancer activity was measured in broccoli florets and microgreens. The cytotoxicity of microgreens extract was confirmed by flow cytometry assays. Significantly higher anticancer activity was observed in microgreens as compared to the florets. The IC50 value for Thp-1 cell line was 772.47 and 446.34 µg mL-1for florets and microgreens, respectively. In cell cycle analysis, 69% cells were arrested at G0/G1 phase. The 8.58% of dead cells were detected in early apoptosis. As the cells were in early apoptosis, DNA damage was observed only in 3.53% cells. Thus, the increased consumption of broccoli microgreens could have significantly positive impact on human health.